Pengaruh Laba Bersih dan Debt To Equity Ratio (DER) terhadap Harga Saham Pada PT. Bisi Internasional, Tbk Periode 2012-2022 - Andi Tabuni; Rudi Ginting; Ida Harahap (Akuntansi, 2024)
This study aims to analyze the effect of net profit and Debt to Equity Ratio (DER) on stock prices at PT. Bisi Internasional Tbk during the period 2012-2022. Net profit and DER were chosen as independent variables because both are important indicators in assessing a company's financial performance and potential investment risk. This study uses multiple linear regression analysis methods to identify the relationship and impact of the two variables on the company's stock price. The results of the study show that net income has a significant positive effect on stock prices, while DER has different effects depending on its level. These findings are expected to provide insight for investors and company management in making investment decisions and financial strategies.